Seamless Roaming Architecture - Yu-Chang Chen; Yi-Ju Liao; Po-Ting Chen (2011 2nd International Conference on Innovations in Bio-Inspired Computing and Applications, 2011)
With the integration of heterogeneous network protocols, roaming among different networks becomes feasible. The subjects with most attention are the guaranteed quality of services (QoS) and the handoffs without disconnections. This paper proposes a roaming node encoding algorithm in wireless communications, in order to define nested network nodes, without duplicate encodings, and to rapidly confirm the existence of the surrounding base stations and the amount of their resources. It also proposes four resource reservation methods - Random Destined, Direction Destined, Walking Path Destined, and Historical Path Destined - to predict the walking path and provide resource reservation services. To solve the problems of resource waste and low utilization due to resource reservation at mobile nodes, we give each direction a competition weight based on its fan-shaped walking patterns, and through this weight a resource reservation competition is performed. In this way, resource utilization is increased and the goal of QoS-guaranteed roaming provided with path prediction and resource reservation is achieved. The paper also verifies the performance of the proposed methods by means of constructing a simulated environment of Taiwan's national highways and county highways.